Production of Lactic Acid from Seaweed Hydrolysates via Lactic Acid Bacteria Fermentation - Lin, Hong-Ting Victor; Huang, Mei-Ying; Kao, Te-Yu; Lu, Wen-Jung; Lin, Hsuan-Ju; Pan, Chorng-Liang (Fermentation (Basel), 2020)
Biodegradable polylactic acid material is manufactured from lactic acid, mainly produced by microbial fermentation. The high production cost of lactic acid still remains the major limitation for its application, indicating that the cost of carbon sources for the production of lactic acid has to be minimized. In addition, a lack of source availability of food crop and lignocellulosic biomass has encouraged researchers and industries to explore new feedstocks for microbial lactic acid fermentation. Seaweeds have attracted considerable attention as a carbon source for microbial fermentation owing to their non-terrestrial origin, fast growth, and photoautotrophic nature. The proximate compositions study of red, brown, and green seaweeds indicated that Gracilaria sp. has the highest carbohydrate content. The conditions were optimized for the saccharification of the seaweeds, and the results indicated that Gracilaria sp. yielded the highest reducing sugar content. Optimal lactic acid fermentation parameters, such as cell inoculum, agitation, and temperature, were determined to be 6% (v/v), 0 rpm, and 30 °C, respectively. Gracilaria sp. hydrolysates fermented by lactic acid bacteria at optimal conditions yielded a final lactic acid concentration of 19.32 g/L.